KNOWLEDGE, ATTITUDES AND PREDICTORS OF CERVICAL CANCER SCREENING UPTAKE AMONG WOMEN IN OYO STATE, NIGERIA (2023)
CervicalCancer(CC),apreventablemalignanttumourinwomen’s cervixes, is one of the most common causes of maternal deaths in developing countries. Despite its preventability through regular Cervical Cancer Screening (CCS), it is the second most common cancer responsible for gynaecological morbidity and mortality in Nigeria. Studies on CC have largely focused on its biomedical contexts, with little attention paid to the social contexts affecting the knowledge and attitudes towards the uptake of Cervical Cancer Screening (CCS). This study, therefore, investigated the awareness, knowledge, attitudes, perceptions of risks, and the socio-cultural factors influencing the uptake of CCS among women in Oyo State, Nigeria. The Health Belief Model was adopted, while the mixed methods, comprising a cross-sectional survey design, was utilised. Oyo State was purposively selected based on the availability of a functional cancer registry. Two Local Government Areas (LGAs) were randomly selected from each of the three senatorial districts. Using Leslie Kish’s (1965) formula, a sample of 960 respondents was determined based on the projected 2019 population of these LGAs. A questionnaire on the socio-economic, attitude, knowledge, perception of the risk factors, and accessibility to screening centres and health workers was systematically administered to women (aged 20-60 years) in the selected LGAs - Oluyole (189), Oyo West (126), Irepo (109), Ogbomosho North (178), Ibarapa-North (91) and Ibadan South-West (267) LGAs. Questionnaire was proportionally administered based on the LGAs’ population. In-depth interviews were conducted with six community leaders, six women and eight religious leaders. Key informant interviews were conducted with four physicians and 12 nurses\midwives. Three focus group discussions were held with married men. The quantitative data was analysed using descriptive statistics, Chi square and multiple regression at p≤0.05, while the qualitative data were content-analysed. The respondents’ age was 34.67±11.91 years, 86.0% earned below ₦45,000 monthly, and 65.3% were married. Awareness of CC was low (38.0%) based on the misconception of its causes, and it varied by income (χ2=14.92), education (χ2=36.77) and employment (χ2=54.87) status. Knowledge about the causes of CC was poor, as 49.3% had knowledge about its symptoms. Socio-cultural factors jointly predicted uptake of CCS (R=0.21, R2 =0.05, Adjusted R2=0.04, (F (4,929) =10.90). Knowledge of CC insignificantly contributed to CCS uptake (β=0.02). Perceived benefit (β=0.54), perceived severity (β=-0.02) and cervical cancer risk perception (β=0.21), independently contributed to the uptake of CCS. More than half (60.0%) had negative attitude towards CCS uptake. Womanhood (62.6%), promiscuity (56.3%), smoking habit (53.7%), and family history (47.0%) were the reported risk factors for CC. A majority of the male discussants associated jejere enu ile-omo with prostitution. The use of herbs, role of diviners, spousal support, and religious beliefs influenced uptake of CCS. The cost of CCS, location of CCS centres, fear of stigmatisation, and perceived pains limited CCS uptake. Poor knowledge and awareness ofcervicalcancernegativelyinfluencedattitudestowardscervicalcancerscreeningamongwomeninOyoState,Nigeria.Amultistakeholderholisticframework to motivate positive awareness and uptake ofcervical cancer screening is recommended.